The Effect of Dividend Payout Ratio, Leverage and Management Ownership on Firm Value - Firdha Rahmiyanti; Rasendria Hanif Pratama (Kajian Akuntansi, 2023)
The purpose of this study is to analyze the effect of Dividend Payout Ratio (DPR), leverage, and managerial ownership on firm value in manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period. The sample selection in this study used a purposive sampling technique as many as 129 companies that entered the research criteria. The test method uses multiple linear regression analysis which is tested statistically and has met the criteria of classical assumptions such as data normally distributed, does not have multicollinearity and heteroscedasticity problems. The results showed that statistically DPR has an effect on firm value with a confidence level of 1%. However, leverage is not proven to have an effect on firm value. The results of this study also succeeded in proving that managerial ownership has an effect on firm value with a confidence level of 5%.Keywords: Dividend Payout Ratio, Leverage, Management Ownership, Firm Value